FOCAL STIMULAL RELATIONS: WORKING WITH THE QUALITY OF LIFE OF MENOPAUSE WOMEN - Hendra, Donny (Jurnal Ilmiah Permas: Jurnal Ilmiah STIKES Kendal, 2020)
Menopause is getting more attention in developed countries besides the health problems that have emerged. With increasing life expectancy as well as the number of women population being transferred at menopause, which was not much discussed at first becomes something very important to be discussed. The purpose of this study was to study the relationship of focal stimuli: with the quality of life of menopausal women in the Pekanbaru City Health Center Work Area. Correlative descriptive research design with cross sectional discussion. The sample of menopausal women was 107 respondents, taken by simple random sampling technique. Data were collected by questionnaire sheet and analyzed by univariate and bivariate. The results of the study obtained from half of the working elderly have a good quality of life (70.9%) and more than half of the elderly who do not work have a poor quality of life (67.1%). From the results of statistical tests it was found that the p value of focal stimulus: The work of the elderly with the quality of life of the elderly is 0,000 (<0.05), so it can be concluded that there is a significant or related relationship between the focal stimulus: The work of the elderly with the quality of life of menopausal women.